2022
DOI: 10.1111/imj.15824
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported child maltreatment and cardiometabolic risk in 30‐year‐old adults

Abstract: Background: Childhood maltreatment (CM) is associated with both dietary fat intake and obesity in later life. There is less information on associations with metabolic risk factors and specific types of CM such as physical, sexual and emotional abuse, as well as neglect.Aims: To assess the association between five types of self-reported CM and a range of obesity and metabolic indicators in a subsample of a birth cohort.Methods: This was a study of 1689 adults born in a major metropolitan maternity hospital in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Participants with a history of ELS were also more likely to have a waist circumference and systolic blood pressure above and HDL levels below the NCEP ATP III-defined clinical cut-points for MetS. These results are consistent with prior studies that have demonstrated an association between ELS and obesity and increased adiposity, lower HDL levels, higher diastolic blood pressure, and higher hemoglobin A 1c in adolescence through mid adulthood (20,23,25,26). Measures of increased adiposity are among the most consistently reported metabolic risk factors associated with ELS, likely due to altered hypothalamic-pituitary-adrenal axis function (8,23), chronic inflammation (10), and health behaviors such as lower dietary quality (37).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Participants with a history of ELS were also more likely to have a waist circumference and systolic blood pressure above and HDL levels below the NCEP ATP III-defined clinical cut-points for MetS. These results are consistent with prior studies that have demonstrated an association between ELS and obesity and increased adiposity, lower HDL levels, higher diastolic blood pressure, and higher hemoglobin A 1c in adolescence through mid adulthood (20,23,25,26). Measures of increased adiposity are among the most consistently reported metabolic risk factors associated with ELS, likely due to altered hypothalamic-pituitary-adrenal axis function (8,23), chronic inflammation (10), and health behaviors such as lower dietary quality (37).…”
Section: Discussionsupporting
confidence: 87%
“…This study adds to a growing body of literature that has identified ELS as a contributor to cardiometabolic risk in young adults and is among the first to examine metabolic risk in this population using a more complete risk assessment, including all the components of MetS criteria and additional other clinical risk factors such as hemoglobin A 1c and LDL cholesterol. Most prior studies in young adults have examined either individual risk factors (25,26) or the clustering of a few metabolic risk factors (10) rather than using composite metabolic risk scores. The clinical cut-point metabolic risk score was designed to include each individual component of MetS criteria, in addition to hemoglobin A 1c , all of which are individually associated with insulin resistance and elevated risk of CVD and T2DM (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations